Tumor-Derived IL33 Promotes Tissue-Resident CD8 + T Cells and Is Required for Checkpoint Blockade Tumor Immunotherapy - Chen, Lujun; Sun, Runzi; Xu, Junchi; Zhai, Wensi; Zhang, Dachuan; Yang, Min; Yue, Cuihua; Chen, Yichao; Li, Song; Turnquist, Heth; Jiang, Jingting; Lu, Binfeng (Cancer immunology research, 2020)
Immune checkpoint blockade (ICB) immunotherapy has revolutionized cancer treatment by prolonging overall survival of patients with cancer. Despite advances in the clinical setting, the immune cellular network in the tumor microenvironment (TME) that mediates such therapy is not well understood. IL33 is highly expressed in normal epithelial cells but downregulated in tumor cells in advanced carcinoma. Here, we showed that IL33 was induced in tumor cells after treatment with ICB such as CTL antigen-4 (CTLA-4) and programmed death-1 (PD-1) mAbs. ST2 signaling in nontumor cells, particularly CD8 T cells, was critical for the antitumor efficacy of ICB immunotherapy. We demonstrated that tumor-derived IL33 was crucial for the antitumor efficacy of checkpoint inhibitors. Mechanistically, IL33 increased the accumulation and effector function of tumor-resident CD103 CD8 T cells, and CD103 expression on CD8 T cells was required for the antitumor efficacy of IL33. In addition, IL33 also increased the numbers of CD103 dendritic cells (DC) in the TME and CD103 DC were required for the antitumor effect of IL33 and accumulation of tumor-infiltrating CD8 T cells. Combination of IL33 with CTLA-4 and PD-1 ICB further prolonged survival of tumor-bearing mice. Our study established that the "danger signal" IL33 was crucial for mediating ICB cancer therapy by promoting tumor-resident adaptive immune responses.